REFLEKSI SPIRITUAL MENGGAPAI PUNCAK TAKWA (KAJIAN TAFSIR TEMATIK MENJALIN KOMUNIKASI BERSAMA ALLAH SWT) - Otong Surasman (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
At a time when the condition of Muslims in facing the challenges of the times, after receiving national and even global examinations with the outbreak of covid-19, made some human beings, especially Muslims, experience complacency in carrying out worship in congregation, because there is a prohibition on keeping a distance in order to avoid the transmission of COVID-19. -19. So the most important move to revive worship and muamalah, it is very important to re-understand his identity as a pious person. Spiritual reflection reaching the pinnacle of piety is a powerful concept. so that Muslims take the time to communicate with Allah SWT through the concept of "Sho Dzi BA Sho", in order to establish a closer intimate relationship with Allah SWT and open horizons of awareness in living life to share with fellow humans as a form of concern for the social life of the community. appear to be generous people. Where there are still many Muslims today, whose lives are below the line of poverty and ignorance, because the main reason is that they are far from the holy book of the Qur'an.